(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the outcomes of scalpel and electrosurgical skin incision in treatment of inguinal hernia. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of Surgery, Services Institute of medical sciences, Lahore from January 2020 to July 2022. Methods: A total of 270 male patients aging between 15 to 80 years planned for unilateral inguinal hernioplasty were divided in to 2 equal groups of 135 patients each. In Group A patients were treated with electrosurgical skin incision while in Group B patients were treated with scalpel skin incision. The primary outcomes were set as postoperative pain, as assessed on visual analogue scale, at 24-hours after the procedure and incidence of hematoma as assessed on day 7 after the surgery. Results: The Mean±SD of age in this study was 47.45±18.93 years with an age range of 15 to 80 years. The results of primary outcomes of the study show that the mean postoperative pain after 24-hour of procedure was significantly less in Group a compared to Group B (3.37 ± 1.81 Vs 4.43 ± 1.94, p-value = 0.00). Similarly, the frequency of hematoma was significantly lower in Group A compared to Group B (5.92% Vs 19.25%, p=0.00). Conclusion: Electrosurgical skin incision provides significantly better outcomes in terms of lesser postoperative pain and lower incidence of hematoma in patients undergoing inguinal hernioplasty.